The Impact of Carotid Artery Stenting on Cerebral Perfusion, Functional Connectivity, and Cognition in Severe Asymptomatic Carotid Stenosis Patients - Wang, Tao; Sun, Dong; Liu, Yumin; Mei, Bin; Li, Huagang; Zhang, Shengming; Zhang, Junjian (Frontiers in Neurology, 2017)
BACKGROUND AND PURPOSE: Asymptomatic carotid artery stenosis can lead to not only stroke but also cognition impairment. Although it has been proven that carotid artery stenting (CAS) can reduce the risk of future strokes, the effect of CAS on cognition are conflicting. In recent years, pulsed arterial spin labeling (pASL) MRI and resting-state functional MRI (R-fMRI) have been employed in cognitive impairment studies. For the present study, cognition is evaluated in severe asymptomatic carotid artery stenosis patients undergoing CAS and the mechanisms underling the cognitive change are explored by pASL MRI and R-fMRI. MATERIALS AND METHODS: We prospectively enrolled 24 asymptomatic, severe (≥70%), unilateral internal carotid artery stenosis patients, who were expecting the intervention of carotid artery stenting. Cognition assessment (including the Montreal Cognitive Assessment Beijing Version, the Minimum Mental State Examination, the Digit Symbol Test, the Rey Auditory Verbal Learning Test, and the Verbal Memory Test) and an integrated MRI program (pASL MRI and R-fMRI) were administered seven days before and three months after CAS. RESULTS: 16 subjects completed the follow-up study. After stenting, significant improvement in the scores of the MMSE, the Verbal Memory test and the delayed recall were found. No significant difference was found in the scores of the Montreal Cognitive Assessment Beijing Version, the Digit Symbol Test and the immediate recall. After CAS treatment, asymptomatic carotid artery stenosis patients showed increased perfusion in the Left Frontal Gyrus, increased amplitude of low-frequency fluctuation (ALFF) in the Right Precentral Gyrus and increased connectivity to the posterior cingulate cortex (PCC) in the Right Supra Frontal Gyrus. However, no significant correlations were found between these imaging changes and cognition assessments. CONCLUSION: Successful CAS can partly improve cognition in asymptomatic carotid artery stenosis patients. The cognition improvement may be partly attributed to the increased perfusion in the Left Frontal Gyrus, increased ALFF in the Right Precentral Gyrus and increased connectivity to the PCC in the Right Supra Frontal Gyrus.